US military language group in signs of language and culture - Angaleva M. A. (Interactive science, 2019)
the relevance of this study is determined by the importance of theoretical and practical analysis of issues related to intercultural communication. The object of this paper is the extralinguistic aspect of the U.S. military lingo. The subject area embraces distinctive linguistic phenomena of the military subcultural milieu, going back to the historical and cultural heritage of military society and thus characterized by extralinguistic context. As exemplified in English, the authors point out, that success of cross-cultural communication is largely determined both by a high level of linguistic competence and background knowledge.
Keywords: межкультурная коммуникация; фоновые знания; военнослужащий; cross-cultural communication; армейская субкультура США; армейский идиом; military subculture; service member; military idiom; background knowledge